Population development in the city of Maribor in the years between 1981 and 2002 - Horvat, Uroš (Journal for Geography, 2006)
The article discusses the characteristics of the population growth in the city of Maribor between 1981 and 2002. The development basically followed the tendencies of other larger Slovene cities. However, the process of depopulation was most intensive in Maribor. In the recent years the tendencies of decrease in the number of inhabitants in Maribor indicate the annual rate of 1.2 %. Maribor has also, compared to other larger cities, the highest age index of population. Due to the influence of various social and economic factors, the demographic circumstances differ from one part of the city to another.